National Culture and Education in Brazil: Tradition and Reform in F. Azevedos?s Thought - Malinowski, Mariusz (INSTED: Interdisciplinary Studies in Education & Society, 2017)
Searching for the true meaning of national culture and identity was one of the most important concerns of Brazilian intellectuals in the first half of the 20th Century. In his works, Fernando de Azevedo (1894?1974) was trying to show the importance of education in the culture-making processes. He also led the action of educational reforms at all levels. The paper outlines the importance of F. Azevedo?s thought in the history of Brazilian education, with special emphasis on how the national tradition should be reproduced in the way of projected reforms.